KAJIAN KELAYAKAN USAHA PENGOLAHAN KERUPUK IKAN PIPIH DI KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Wahdah Wahdah; Emmy Sri Mahreda; Emmy Lilimantik (EnviroScienteae, 2016)
This research aimed to (1) analyze the market opportunity of the giant featherback crackers processing business in Barito Kuala Regency; (2) analyze the profit of the giant featherback crackers processing business in Barito Kuala Regency; and (3) analyze the investment feasibility of the giant featherback crackers processing business in Barito Kuala Regency.     This research was carried out in Bahalayung and Lapasan Villages, Bakumpai District, Barito Kuala Regency, South Kalimantan, with the objects of the giant featherback crackers processors. The data that was collected was the data that directly originated from results of observation in the location of the research, and the other supporting data was related to the object of the research. Results of the research showed that the demand of the giant featherback crackers in Barito Kuala Regency was about 36 ton per the year, with the mean supply of the giant featherback crackers was about 6 ton per the year, so that the giant featherback crackers processing business still owned the market opportunity as many as 30 tons per the year. The giant featherback crackers processing business could give the profit about Rp.6,893,000 - Rp.12,930,000 per the year or about Rp.19,147 - Rp.21,550 per kg with the production about 360 - 600 kg.  The giant featherback crackers processing business in Barito Kuala Regency was profitable and feasible to be carried on, considering the Net Present Value was positive and the Net BCR that more than one, as well as the business was still beneficial was limited by the interest did not reach 137% with the period of the return of investment till 0.71 years (faster than the project period during five years).